Dose-response study of sodium cromoglycate in exercise-induced asthma. - Patel, K R (1982)
Ten patients with exercise-induced asthma participated in a single-blind dose-response study comparing the protective effect of inhaled sodium cromoglycate in increasing concentrations from 2 to 40 mg/ml. Saline was used as a control. Effects were assessed from the mean maximal percentage fall in forced expiratory volume in one second (FEV1) after the patients had run on a treadmill for eight minutes. There was slight bronchodilation evident from the increase in baseline FEV1 after inhalation of sodium cromoglycate, the difference reaching statistical significance with the highest concentration (5.7%, p less than 0.05). After exercise the maximal percentage falls in FEV1 (means and SEM) after saline and after sodium cromoglycate at 2, 10, 20, and 40 mg/ml were 37.3 +/- 4.7, 17.3 +/- 4.1, 10 +/- 3.3, 7.6 +/- 2.4, and 12 +/- 2.9. Sodium cromoglycate inhibited the exercise-induced fall in FEV1 at all the concentrations used in the study (p less than 0.001) and its inhibitory effect increased from 2 to 20 mg/ml. The mean FEV1 returned to baseline values within 15 minutes at higher concentrations of sodium cromoglycate (20 and 40 mg/ml) and a small bronchodilator effect was noted at 30 minutes. The findings suggest that the protective effect of sodium cromoglycate in exercise asthma is dose related. At higher concentration the drug suppresses chemical mediator release from the lung mast cells and may also modify the bronchial reactivity to release mediators.